A new Blepharosis species from China (Lepidoptera, Noctuidae) - Gyulai, Peter; Saldaitis, Aidas; Truuverk, Andro; Vaitonis, Gintas (Zootaxa, 2019)
In 2017 the second author encountered a rather small Noctuidae species in western Sichuan (China) with unicolorous brown forewings and ochre reniform stigmata. Initially the six males collected resembled the taxa of the genus Cerapteryx Curtis, 1833, but the more gracile body, the finely serrate (and not bipectinated) male antennae and the late flight period indicated the need of further study. Dissection of the male genitalia revealed that the peculiar species belongs to the genus Blepharosis Boursin, 1964. The most recent review with descriptions of new Blepharosis taxa is available from Hreblay, Ronkay & Plante (1998). Comparison of external and genitalia features of the newly found taxon with the known species confirmed that it represents an undescribed species, which is very different externally from all but one of the members of Blepharosis. Regarding the configuration of the male genitalia, the only similar species is Blepharosis anachoretoides (Alphéraky, 1892), displaying only surprisingly small differences between the two species. The large difference between their barcodes (13.5% difference in the COI sequences) indicate however their specific distinctness despite their similar male genitalia structures.